Evaluation of Piperine as Natural Coformer for Eutectics Preparation of Drugs Used in the Treatment of Cardiovascular Diseases - Wilhelm-Romero, K (2022)
Piperine (PIP) was evaluated as a natural coformer in the preparation of multicomponent organic materials for enhancing solubility and dissolution rate of the poorly water-soluble drugs: curcumin (CUR), lovastatin (LOV), and irbesartan (IBS). A screening based on liquid assisted grinding technique was performed using 1:1 drug-PIP molar ratio mixtures, followed by differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD) analyses. Three eutectic mixtures (EMs) composed of CUR-PIP, LOV-PIP, and IBS-PIP were obtained. Therefore, binary phase and Tamman's diagrams were constructed for each system to obtain the exact eutectic composition, which was 0.41:0.59, 0.29:0.71, and 0.31:0.69 for CUR-PIP, LOV-PIP, and IBS-PIP, respectively. Further, bulk materials of each system were prepared to characterize them through DSC, PXRD fully, Fourier transform infrared spectroscopy (FT-IR), and solution-state nuclear magnetic resonance (NMR) spectroscopy. In addition, the contact angle, solubility, and dissolution rate of each system were evaluated. The preserved characteristic in the PXRD patterns and FT-IR spectra of the bulk material of each system confirmed the formation of EM mixture without molecular interaction in solid-state. The formation of EM resulted in improved aqueous solubility and dissolution rate associated with the increased wettability observed by the decrease in contact angle. In addition, solution NMR analyses of CUR-PIP, LOV-PIP, and IBS-PIP suggested no significant intermolecular interactions in solution between the components of the EM. Hence, this study concludes that PIP could be an effective coformer to improve the solubility and dissolution rate of CUR, LOV, and IBS.